Materials, Technologies and Clinical Applications - Baino, Francesco (IntechOpen, 2017)
Biomaterials are often designed to act as scaffolds, i.e., 3D porous templates that support and stimulate the growth of healthy tissue and then safely dissolve once they have performed their functions. This book provides a picture of the current state of the art in the field of scaffolds for tissue engineering, highlighting the potential associated to the latest scientific and technological advancements. The former part of the book focuses on the repair of "hard" tissues (primarily bone) by means of bioceramic/glass scaffolds, and the latter deals with the applications of polymeric scaffolds for regenerating "soft" tissues and structures including the peripheral nerve, heart, gastric mucosa and pancreas. Special emphasis is given to the challenges associated to scaffold manufacturing, biomimetic properties and cell-scaffold interactions.